THE INFORMATION ASYMMETRY AND TENDENCIES OF THE MARKET OF SCIENTIFIC PUBLICATIONS - Ekaterina I. Trubnikova (Высшее образование в России, 2017)
The article represents the analysis of the market of scientific publications and consequences of information asymmetry in this market. Attention is paid to the participants of the market, including different kinds of middle-men that facilitate the interactions between authors and publishers. The purpose of the article is to clarify particular characteristics of the market, which might be helpful for researchers in the process of publication. Nowadays, we observe the expanding gap between levels of signals of universities and researchers from different countries, resulting in different levels of incomes and opportunities for access to scientific knowledge. The article points out that the current system leads to the growth of power of major players of this market, and this is the result of concentration of property rights within the industry.